Filsafat Pendidikan Islam dalam Perspektif Rekonstruksi Pemikiran Kritis untuk Menjawab Tantangan Modernitas - Ridwan Hermawan; Yurna Yurna; Nisa Putri Wulandari; Emat Muslihat; Hasbulloh Karim Alfauzi; Nawil Hadad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The challenges of modernity, including the secularization of knowledge, the fragmentation of values, and the increasingly pragmatic and utilitarian orientation of education, require a fundamental renewal of Islamic educational philosophy. In practice, Islamic education is often confined to normative and textualistic approaches that emphasize the transmission of doctrinal knowledge, which limits its responsiveness to social dynamics, scientific developments, and contemporary needs. This condition weakens the critical capacity of Islamic education in shaping individuals who are faithful, rational, and morally integrated. Accordingly, this study aims to examine Islamic educational philosophy from the perspective of critical thought reconstruction as an effort to address the challenges of modernity without shifting the fundamental principles of faith that serve as its normative foundation. This study employs a theoretical research approach through library research, using qualitative analysis of academic books, peer-reviewed journal articles, and relevant scholarly works on Islamic educational philosophy and critical thought. The analysis focuses on the ontological, epistemological, and axiological dimensions of Islamic education within the framework of critical reconstruction. The findings indicate that the reconstruction of Islamic educational philosophy is both an epistemological and practical necessity in responding to modern challenges. This reconstruction is not directed toward the domain of ʿaqīdah, which is qaṭʿī and normative in nature, but rather toward renewing modes of thinking, operational value systems, and educational practices. Consequently, Islamic education should function not merely at a normative level but as an effective instrument for individual and social transformation.